2014
DOI: 10.1186/s40649-014-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the longitudinal impact of proximity, location, and personality on smartphone usage

Abstract: Background: Over the past few years, mobile devices, particularly smartphones have seen dramatic increases in data consumption. The significant increases in data usage have placed tremendous strain on the wireless infrastructure, necessitating research across a variety of optimization, efficiency, and capacity improvements. Complementary to those research efforts is the acquisition of a better understanding of what aspects drive user smartphone usage. Methods: In this paper, we leverage the unique characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Figure 5(a) is an example of how browsed applications and current location related to each other from the view of temporal and spatial regularity. It has been found that the mobility behaviors have strong influences on online browsing behavior [149,153,154]. Similar trends can also be observed for crowds at crowd gathering places, as is shown in Figure 5(b); i.e., certain apps are favored at places that group people together and provide some specific functions.…”
Section: Analyses Of Human Online and Offline Behavior Based On Mobilsupporting
confidence: 63%
See 2 more Smart Citations
“…Figure 5(a) is an example of how browsed applications and current location related to each other from the view of temporal and spatial regularity. It has been found that the mobility behaviors have strong influences on online browsing behavior [149,153,154]. Similar trends can also be observed for crowds at crowd gathering places, as is shown in Figure 5(b); i.e., certain apps are favored at places that group people together and provide some specific functions.…”
Section: Analyses Of Human Online and Offline Behavior Based On Mobilsupporting
confidence: 63%
“…It is discovered that the more the number of distinct cells a user visit, the more diverse applications user has visited. Zheng et al [153] analyze the longitudinal impact of proximity density, personality, and location on smartphone traffic consumption. In particular, location has been proven to have strong influences on what kinds of apps users prefer to use [149,153].…”
Section: Analyses Of Human Online and Offline Behavior Based On Mobilmentioning
confidence: 99%
See 1 more Smart Citation